Salivary, serum, and abomasal mucus IgA as an immune correlate of protection against Haemonchus contortus infection in naturally infected lambs - Salgado, Jordana Andrioli (2022)
This study aimed to evaluate salivary, serum, and abomasal mucus IgA levels in lambs naturally infected with Haemonchus contortus. Thirty-seven crossbred lambs (½ Texel or ½ Ile de France) with an average age of 193 days were evaluated for 56 days after grazing on a contaminated pasture. Fecal samples were collected every 7 days to evaluate the EPG. Blood and saliva samples were collected for IgA measurement every 14 days. On D56, 29 animals were killed for parasite counting and IgA quantification in the abomasal mucus. Salivary, serum, and abomasal mucus IgA were measured by ELISA using third-stage larvae antigens. Salivary and mucus IgA were not correlated, but D14 salivary IgA correlated with EPG on D28 (r = −0.37) and D56 (r = −0.36); D28 salivary IgA correlated with D49 (r = −0.40) and D56 EPG (r = −0.44). Abomasal mucus IgA negatively correlated with EPG from D28 to D56 (r varied from _0.51 to −0.62) and with the counts of all parasitic stages (−0.60 to −0.67). The lambs were classified as susceptible (S) or resistant (R) according to EPG (D56 EPG and cumulative EPG) or IgA (salivary, serum, and mucus IgA). Based on D56 EPG and cumulative EPG, resistant lambs had higher D14 salivary IgA, mucus IgA, and total worm counts. For evaluations based on IgA levels, the EPG of S and R animals differed, indicating that IgA was an immune correlate of protection against natural infection with Haemonchus sp., mainly in the saliva sample of D14.